Kardashians : a critical anthology - Jones, Meredith (Meredith Rachael), 1965-; Burton, Kath; Brien, Donna Lee, 1959- (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"This interdisciplinary volume introduces the field of Kardashian Studies through collections of essays based in sociology, media studies, cultural studies, critical race theory, and fashion theory. The Kardashian empire and dynasty is intertwined with some of the most important movements of the early 21st century. Celebrity, cultural appropriation, new forms of feminism, social media, ideal bodies, evolving notions of physical beauty, and the global fashion system have all been affected by the quintessential influencers in this family of matriarchs. The anthology is structured around core thematic sections. From Storytelling and Race through Fashion and Celebrity to Time and Embodiment, each section contains an accessible introduction followed by chapters that together take a unique approach to exploring the Kardashians from multiple viewpoints. The inclusion of discussion points suitable for classroom use enhances the utility of the anthology for both study and teaching purposes. The first of its kind, Kardashians: A Critical Anthology positions Kardashian Studies at the forefront of critical inquiry around notions of authenticity, contemporary feminisms, visuality and social media. It will of interest to both scholars and students interested in popular culture, television, notions of authenticity, contemporary feminisms, visuality, race, and social media"--
Introduction: Kuriously kritical : Kardashians as cyborg goddesses / Meredith Jones -- Family brands : the Kardashian-Jenners and the Nelsons / Cynthia B. Meyers -- The performance of authorship in published books by the Kardashians and Jenners / Donna Lee Brien -- Selfish : a happy archive? / Laura Henderson Child -- There is no sexual relation : the Kardashians and Black masculinities / Manuel Harpin -- Kim Kardashian's "kimono" : the complexities of cultural appropriation / Jenny Hall -- White multiracial sentiment / Ren Ellis Neyra -- SKIMS : body-positive or Kimspiraton? / Katherine Appleford -- Glitter and the death drive : Kim Kardashian's Met Gala costumes / Meredith Jones -- The corporeality of reproduction, and surrogate pregnancy in Keeping up with the Kardashians / Siri Lindholm -- "It's super disgusting" : an analysis of famous cis-men responses to the Kardashian's deviant femininity / Oline Eaton -- Where has all the affect gone on Kardashian reality TV? : negotiating emotional labour and boundaries / Meera Govindasamy -- Debunking celebrity activism : Kim Kardashian and prison advocacy / Lida Papakonstantinou -- The role of transgender celebrities : the power of representation / Cavyn Mitchell -- In the lab with the Kardashians : how Kardashian-linked research finds its audience / Michael Taylor and Carlos Areia -- The Kardashians will never die : on repetition and infinity / Phoebe Kaufman -- Use of artificial intelligence and holography : Robert Kardashian resurrected? / Lida Papakonstantinou -- Keeping up with the past, present and future : how the Kardashians sustain relevancy by manipulating reality / Ruby Smith.
Keywords: Kardashian family; Keeping up with the Kardashians (Television program); Television personalities -- United States; Internet personalities -- United States; Celebrities -- United States; Reality television programs -- United States History and criticism; SOCIAL SCIENCE / Media Studies